2020
DOI: 10.21203/rs.3.rs-17866/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Echocardiographic Reference Intervals with Allometric Scaling of 823 Clinically Healthy Rhesus Macaques (Macaca Mulatta)

Abstract: Background: Echocardiography is commonly used for assessing cardiac structure and function in various species including non-human primates. A few previous studies reported normal echocardiographic reference intervals of clinically healthy rhesus macaques under sedation. However, these studies were under-powered, and the techniques were not standardized. In addition, body weight, age, and sex matched reference intervals should be established as echocardiographic measurements are commonly influenced by these var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 25 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…Electrophysiological assessments have suggested that cardiac functions are similar between humans and cynomolgus monkeys [2]. Only a few reports have described echocardiographic reference values for cynomolgus monkeys [18,29,32,36], and standardized echocardiographic reference values are incomplete, because those studies used small colonies and monkeys with a limited age range. However, echocardiography offers a graphic, real-time means of intravital imaging and has more potential for diagnosis than electrocardiography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Electrophysiological assessments have suggested that cardiac functions are similar between humans and cynomolgus monkeys [2]. Only a few reports have described echocardiographic reference values for cynomolgus monkeys [18,29,32,36], and standardized echocardiographic reference values are incomplete, because those studies used small colonies and monkeys with a limited age range. However, echocardiography offers a graphic, real-time means of intravital imaging and has more potential for diagnosis than electrocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Nonhuman primates are optimal experimental animals because of their similarity to humans in terms of anatomy and physiology. In addition, their cardiovascular system resembles that of humans and their body size is appropriate for examinations; thus, experimental monkeys are necessary to develop cardiovascular medicines for humans [1,29,36]. In addition, general aging and growth patterns of monkeys, including cynomolgus monkeys (Macaca fascicularis) resemble those of humans, while the rate of aging in these monkeys is 3 times that in humans [26,37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few previous studies reported normal echocardiographic reference ranges of clinically healthy rhesus macaques under sedation [ 1 , 2 ]. In addition, the authors of the present study reported echocardiographic reference intervals in geriatric rhesus macaques older than 18 years [ 3 ]. These studies reported that the reference intervals of various echocardiographic parameters in geriatric rhesus macaques are different from those in younger adult rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%